1998
DOI: 10.1046/j.1365-3024.1998.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo expression of cytokine mRNA in rats infected with Schistosoma mansoni

Abstract: As an animal model, rat schistosomiasis mansoni has provided considerable knowledge of immune mechanisms involved in the expulsion of worms and in a subsequent development of immunity to reinfection. Although it is clear that ADCC mechanisms participate in immunity to reinfection; the nature of the cytokines involved in immunity is unknown. To analyse the pattern of cytokines involved, the mRNA levels of different cytokines were assessed by RT-PCR as they occur within tissues during the course of infection. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…[18][19][20][21] According to Cêtre et al, the unexpected increase in splenic IL-2 without an increase in IFN-c might be due to lymphoproliferation after an antigenic stimulation. 28 Although in the present study no quantitative method was used to count splenic lymphocytes, proliferation of leucocytes within the spleen is suggested by the overall increase in splenic MPO activity after infection with S mansoni, irrespective of the presence of TNBS induced colitis. The reason for the isolated increase in splenic IL-2 in the rat after S mansoni infection remains largely unexplained.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…[18][19][20][21] According to Cêtre et al, the unexpected increase in splenic IL-2 without an increase in IFN-c might be due to lymphoproliferation after an antigenic stimulation. 28 Although in the present study no quantitative method was used to count splenic lymphocytes, proliferation of leucocytes within the spleen is suggested by the overall increase in splenic MPO activity after infection with S mansoni, irrespective of the presence of TNBS induced colitis. The reason for the isolated increase in splenic IL-2 in the rat after S mansoni infection remains largely unexplained.…”
Section: Discussionmentioning
confidence: 70%
“…It was previously shown that S mansoni induces a Th2 immune response in the semipermissive rat host. 28 In general, the systemic immune response to S mansoni in rodents can be followed by measuring cytokine production in the lungs, liver, spleen, or mesenteric lymph nodes. 28 In the present study, we evaluated the systemic immune response by analysing cytokine production in the spleen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicates that the immune response is associated to the parasitic infection pathway (Cetre et al, 1998). C. hepatica is a parasite, which is largely unrelated to MLNs, parasitic in the liver parenchyma and requires only a short time to pass the intestine.…”
Section: Discussionmentioning
confidence: 92%
“…In support of this, we have recently analyzed the mechanisms of protective immunity developed during rat experimental schistosomiasis. Interestingly, these data indicate major differences with mouse model regarding the type and the nature of immune protective response (23,24). Collectively, observations made in rat model and humans, and unlike mouse model, demonstrated strong similarity since a type 2 response is predominantly involved in protection against schistosomiasis (25).…”
mentioning
confidence: 99%